EMBODIED AND EXBODIED MIND: WHAT IN BETWEEN WHEN BODY IMAGE AND BODY SCHEMA (DE)-CONNECT? - Zatti, Alberto; Riva, Nicoletta (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
When social and clinical psychology “work together,” cultural-based disturbs, like eating disorder behaviour, can be seen in a new light. Self-image is a perception product based on icon memory, imagination, sensory stimulus, social context expectations, self-beliefs about social context adequacy, etc. Still, it is also based on self-representation, like dress, fashion, maquillage, etc. A different discourse can be done for what psychology intends for body schema. Body gesture, movement, and action result from very complex different neural systems cooperation, combining sensory and motor brain centres. Training to build neuro-motor schemas requires a very long time and effort, as in each human art like dance, sports, playing drama, art crafts competencies, etc. What if one’s body image and body schema are unbalanced? If the social body image pressure will bring one’s total mimesis with it or to an original, personal interpretation is here attributed to the “exboding” capacity, coming from a “sufficient” balance between body schema and body image.Some anorexia nervosa patients are frequently engaged in intense physical activities. In our interpretation, their conscious control of the body comes from the social colonisation of embodied images that produce a disequilibrium between body image and body schema. Thus, a sort of “body-image” liberation could be possible if a deep awareness of our body schema is reached. The central hypothesis of this work is that the embodiment processes, primarily dependent on cultural pressure, have to be seen in unstable equilibrium with exbodiment experiences, which can be considered as the expression of body schema originated by personal sensory-motor history (see References 1; 2; 3). To evaluate the possible separation between the two, a new picture questionnaire has been elaborated. Dysmorphic "confusion" is widely spreading in contemporary Western societies, particularly among adolescents (4; 5). The perception of how we are seen by others (body image) is one of the core issues in social trends, education, and psychopathology (6).  On the other hand, what one implicitly knows of his/her somatic body (body schema) represents the psychological antecedent basis implied in social interaction (2). This article attempts to give a quantitative dimension to the two sides of the body, the structural, implicit one (body-schema) and the public, partly self-controlled one (body-image).